Light-level geolocators reveal migratory connectivity in European populations of pied flycatchers Ficedula hypoleuca - Ouwehand, J.; Ahola, M. P.; Ausems, A. N. M. A.; Bridge, E. S.; Burgess, M.; Hahn, S.; Hewson, S. M.; Klaassen, R. H. G.; Laaksonen, T.; Lampe, H. M.; Velmala, W.; Both, C. (Wiley-Blackwell, 2016)
Understanding what drives or prevents long-distance migrants to respond to environmental change requires basic knowledge about the wintering and breeding grounds, and the timing of movements between them. Both strong and weak migratory connectivity have been reported for Palearctic passerines wintering in Africa, but this remains unknown for most species. We investigated whether pied flycatchers Ficedula hypoleuca from different breeding populations also differ in wintering locations in west-Africa. Light-level geolocator data revealed that flycatchers from different breeding populations travelled to different wintering sites, despite similarity in routes during most of the autumn migration. We found support for strong migratory connectivity showing an unexpected pattern: individuals breeding in Fennoscandia (S-Finland and S-Norway) wintered further west compared to individuals breeding at more southern latitudes in the Netherlands and SW-United Kingdom. The same pattern was found in ring recovery data from sub-Saharan Africa of individuals with confirmed breeding origin. Furthermore, population-specific migratory connectivity was associated with geographical variation in breeding and migration phenology: birds from populations which breed and migrate earlier wintered further east than birds from late' populations. There was no indication that wintering locations were affected by geolocation deployment, as we found high repeatability and consistency in C-13 and N-15 stable isotope ratios of winter grown feathers of individuals with and without a geolocator. We discuss the potential ecological factors causing such an unexpected pattern of migratory connectivity. We hypothesise that population differences in wintering longitudes of pied flycatchers result from geographical variation in breeding phenology and the timing of fuelling for spring migration at the wintering grounds. Future research should aim at describing how temporal dynamics in food availability across the wintering range affects migration, wintering distribution and populations' capacity to respond to environmental changes.
Keywords: ornithology; zoology; palearctic migrants; habitat selection; birds; songbird; winter; repeatability; determinants; isotopes; duration; West-Africa